2019
DOI: 10.1016/j.mjafi.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of effects of intrapleural block with adjuvants on analgesia and pulmonary function after intercostal drainage: A pilot study

Abstract: Background: Inter-costal chest drain (ICD) used for varied thoracic pathologies causes continuous pain and irritation of the pleura, which limits respiratory efforts and impairs ventilatory function. Intrapleural block deposits local anaesthetic between the layers of pleura and may improve ventilatory function especially in non surgical patients. Methods: Twenty eight ASA I-III patients treated with ICD, who could perform incentive spirometry, were included for study. They were randomized to 'Group C' (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies on cadavers showed that Indian ink spread from the parietal pleura into the peripleural area and returned to several intercostal nerves. This served as the foundation for our study’s positioning methodology [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cadavers showed that Indian ink spread from the parietal pleura into the peripleural area and returned to several intercostal nerves. This served as the foundation for our study’s positioning methodology [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%